2011
DOI: 10.1128/iai.05109-11
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Activates Calpain via Toll-Like Receptor 2 To Disrupt Adherens Junctions in Human Gastric Epithelial Cells

Abstract: Helicobacter pylori is a risk factor for the development of gastritis, gastroduodenal ulcers, and gastric adenocarcinoma. H. pylori-induced disruption of epithelial adherens junctions (AJs) is thought to promote the development of severe disease; however, the mechanisms whereby H. pylori alters AJ structure remain incompletely understood. The present study demonstrates that H. pylori infection in human patients is associated with elevated serum levels of an 80-kDa E-cadherin ectodomain, whose presence is indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
(66 reference statements)
1
25
0
Order By: Relevance
“…Studies conducted by us, as well as previous reports showed that H. pylori reduces E-cadherin protein levels and disrupts the adherens junctions [14, 15]. Exposure to H. pylori also induced p38 and JNK kinases.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Studies conducted by us, as well as previous reports showed that H. pylori reduces E-cadherin protein levels and disrupts the adherens junctions [14, 15]. Exposure to H. pylori also induced p38 and JNK kinases.…”
Section: Discussionsupporting
confidence: 66%
“…E-cadherin is a component of the adherens junctions that regulates cell-cell adhesion, intracellular signaling, cell polarity, and proliferation [10, 13]. H. pylori infection has shown to acutely cleave E-cadherin and disrupt the adherens junctions [14, 15]. H. pylori infection can also decrease expression of E-cadherin by promoting hypermethylation of the E-cadherin gene ( CDH1 ) that can be reversed by eradication of the bacteria [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…CagA also inhibits the polarity regulator PAR1b/MARK2 kinase, which causes a loss of epithelial cell polarity and plays a role in the disruption of normal epithelial architecture [Hatakeyama, 2008]. Another hypothesized mechanism for disruption of adherens junctions within gastric epithelial cells is a H. pylori surface protein‐TLR (toll‐like receptor) 2‐induced activation of the protease calpain, which cleaves E‐cadherin and allows for increased β‐catenin signaling [O'Connor et al, 2011].…”
Section: Pathogenicity Of H Pylorimentioning
confidence: 99%
“…It will be of interest to expand this observation to larger cohorts, and especially with longitudinal follow-up. H. pylori -induced calpain activation results in cleavage of E-cadherin to produce a truncated form and induce relocalization of E-cadherin and β-catenin and inhibition of TLR2 prevented H. pylori -induced calpain activation and adherens junctions (AJ) disassembly 41 . O′Connor suggested H. pylori activates calpain via TLR2 to disrupt gastric epithelial AJ structure—in turn, the disruption of AJ structure favors severe disease 41 .…”
Section: Discussionmentioning
confidence: 99%